4⋅f(6)−6⋅g(5) need help asap
![4f66g5 need help asap class=](https://us-static.z-dn.net/files/d8c/9cc8db8adb761c98107d48f9efcac3f1.png)
Answer:
6
Step-by-step explanation:
From the blue graph of f(x) we can see that the function value is -6 when x = 6. Similarly, g(5) = -5.
Then: 4*f(6) - 6*g(5) becomes:
4*(-6) - 6*(-5), or
-24 + 30 = 6
The value of ⋅f(6)−6⋅g(5)= 6
An operation where two functions say f and g generate a new function say h in such a way that h(x) = g(f(x)).
Given:
From the blue graph we can see that
f(x)= -6 when x = 6.
Similarly, g(5) = -5.
thus,
4*f(6) - 6*g(5)
=3 4*(-6) - 6*(-5)
=-24 + 30
= 6
Learn more about this concept here:
https://brainly.com/question/20379727
#SPJ2